DIMENSI METRIK PADA GRAF HASIL KALI SISIR PADA GRAF LINTASAN TERHADAP BEBERAPA GRAF REGULER - Padoma, Widya Aprilia; Gafur, Anuwar Kadir Abdul (Amalgamasi: Journal of Mathematics and Applications, 2025)
Let  be a graphs finite, simple, and connected. A set of vertices  subset of . For , a representation of  with respect to  is defined as -tuple . The set  is a resolving set of  if ever two distinct vertices  satisfy  A basis of  is a resolving set of  with minimum cardinality, and the metric dimension of  refers to its cardinality, denoted by . In this research, Suhadi W Saputro et al have found the metric dimension of the comb product graph  if  leaf or  jika not a leaf. Therefore, we will be looking for the metric dimension of the product of a comb on a path graph to some regular graph and we have managed to find if the copy vertices of . For , let  is a path end  is -regular or  is -regular.  Then for  or  for